An Exploration of AI-Assisted Tools in the Education of Children with Autism from the Perspective of Inclusive Education - Yan, Yili; Liu, Yue (IC-ITECHS, 2024)
With the rapid development of Artificial Intelligence (AI) technology and its widespread use in education, it is becoming increasingly feasible to build more personalized and supportive learning environments for children with autism. The aim of this paper is to explore how AI-assisted tools can promote inclusive education, with a particular focus on the specific group of children with autism. Through keyword searches of relevant papers in mainstream conferences and journals, as well as a comprehensive analysis of existing literature and case studies, we have conducted a systematic review of AI as an aid to promote inclusive education, aiming to provide valuable references for subsequent research. Studies have shown that when AI technology is appropriately applied, it can significantly enhance the social interaction skills, emotional regulation, and academic performance of children with autism. However, it is important to note that most of the current research findings focus on work published within the last few years, and thus may not fully cover relevant contributions from earlier periods. In summary, by examining the current situation of AI applied to the education of children with autism in China, we can see that AI as an assistive tool shows great potential for development and plays a crucial role in realizing inclusive education in the true sense of the word. This not only promotes educational equity, but also provides more opportunities for each child to grow.